Gradišče na Miklavškem hribu nad Celjem - Bolta, L. (Arheološki vestnik, 1951)
On a hill at Celje (Miklavški hrib) under a castle fragments of pottery were discovered; they belong to the Hallstadt-Ulyrian period. Originally, the castle may have served as a place of refuge yet later it was abandonned